Dutch municipal elections 1998-2018: more localism and fragmentation - Raymond Gradus; Elbert Dijkgraaf; Tjerk Budding (Tinbergen Institute, 2020)
Exploring the outcome of Dutch municipal elections between 1998 and 2018, this paper finds two dominant trends: increasing political fragmentation and localism. When explaining localism, the number of inhabitants, regional diversity and the election year dummies are significant. The last result gives some indication for a welfare hypothesis as a large decentralisation of Dutch social policy took place in 2007 and 2015. Some evidence is found for a merger effect of more or less equal municipalities. There is evidence as well that more fragmentation in the municipal council leads to more aldermen. The number of aldermen is also depending on the number of inhabitants and a merger effect in case of two municipalities.
Keywords: H76; D72; 330; local elections; political fragmentation; localism; empirical research